Interest rate pass-through asymmetry: A meta-analytical approach - Tersoo David Iorngurum (Charles University in Prague, Institute of Economic Studies (IES), 2024)
The interest rate pass-through represents a vital transmission mechanism between the financial sector and the real economy. Nonetheless, the empirical literature offers no consensus regarding the direction and extent of asymmetry in this pass-through. In this paper, I systematically review the empirical literature using various contemporary meta-analytic techniques to test for publication bias and establish consensus for the conflicting study outcomes. I find evidence of publication bias. Beyond publication bias, the magnitude of the reported pass-through declines relative to the simple literature average, but substantial asymmetry remains. Precisely, bank lending rates appear to be a lot more responsive to increases than decreases in monetary policy interest rates. Furthermore, I identify the factors responsible for diverse study outcomes. These include study characteristics, asymmetry, and macrofinancial variables. Concerning study characteristics, results differ due to differences in data frequency, data source, the researched period, study quality, author affiliation, and estimation context. Concerning macrofinancial factors, results differ due to differences in openness to foreign direct investment inflows, openness to trade, the inflationary environment, and economic development status. The pass-through is particularly strong in countries more open to foreign direct investment inflows and developed economies but relatively weak for countries more open to import trade and countries with a high inflationary environment. Finally, I model the interest rate pass-through based on the best practices in the literature. On average, the short-run pass-through to bank lending rates is about 49.7% for a policy rate hike and about 29.7% for a policy rate cut. On the other hand, the long-run pass-throughs are about 69.6% and 46.6%, respectively.
Keywords: E43; 330; Interest rate pass-through; asymmetry; meta-analysis